The Effect of Dhuha Study Activities on the Spiritual Intelligence of Students of Padang State University - Ghani, M.; Sulaiman, Sulaiman (Lembaga Yasin AlSys, 2023)
The background of this research is that the value of dhuha study activities on the Spiritual Intelligence of Padang State University Students is unknown. Therefore, the Qatulistiwa Islam Spiritual Activities Unit, Padang State University, is holding a dhuha study activity. This study aims to determine the effect of dhuha study activities on the spiritual intelligence of Padang State University students. This study uses a quantitative method. The method in this study uses a correlational quantitative method which is a type of non-experimental research method in which the researcher measures two variables, and understands and assesses the statistical relationship between the variables, without the influence of extraneous variables. The population of this study were all students of Padang State University who had participated in the Dhuha Study Activities totaling 937 people in the July-December 2022 and January-June 2023 semesters. The sample of this study was 90 students who had participated in the Dhuha study activities in the July-December 2022 and January-December 2022 semesters. June 2023. This research explains that the Islamic Dhuha Qatulistiwa Study Activity influences the Spiritual Intelligence of Padang State University students. Research explains that the value of dhuha study activities and the value of spiritual intelligence has a relationship with the results of SPSS statistics version 29 of the normality test of 0.008, meaning that the significance value is greater than α (0.008 > 0.05) meaning that the data is normally distributed. A simple linear regression test of the Dhuha study activity variable (X) obtained a value of dhuha study activities of 6,824, this is The independent variable Dhuha study activities (X) on Padang State University students has a positive effect. Spiritual intelligence results in a normality test value of 0.158 > 0.05 meaning that the data is normally distributed, a simple linear regression test for the spiritual intelligence variable (Y) gets a value of 1,220, this is the dependent variable Spiritual Intelligence (Y) for Padang State University Students has a positive effect. Influence on the Spiritual Intelligence of Padang State University students. F count = 252,654> F table 3,099 or a Sig of 0.000 < 0.05 which means H0 is rejected and Ha is accepted. The simultaneous significant test produces a calculated F value = 252,654> F table 3,099 or a Sig of 0.000 <0.05 which means H0 is rejected and Ha is accepted. As well as the results of the test for the coefficient of determination, which obtained an R Squer value of 0.742, which means the influence of the independent variable (Dhuha Study Activity) of 74.2% on the dependent variable (Spiritual Intelligence). While the remaining 25.8 % is influenced by other factors outside the research.